2016
DOI: 10.18043/ncm.77.6.402
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Women Against Human Papillomavirus: Benefits, Barriers, and Evidence-Based Strategies to Increase Vaccine Uptake

Abstract: Human papillomavirus (HPV) infection significantly impacts women, as it can cause cancers and precancers of the cervix, vulva, vagina, oropharynx, and anus. However, many of these cancers can be prevented by HPV vaccination. Despite evidence of vaccine effectiveness and safety, vaccination rates remain low. Evidence-based strategies should be utilized to reduce barriers and increase vaccination rates. Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States. Approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…HPV is the most common sexually transmitted infection that causes cervical cancer. It contributes to 17,600 known cases of cervical cancer in women annually [46,47]. While HPV vaccination, early detection, and treatment of this virus can help women prevent its longterm and life-threatening effects, few women have the necessary knowledge and awareness to do so.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is the most common sexually transmitted infection that causes cervical cancer. It contributes to 17,600 known cases of cervical cancer in women annually [46,47]. While HPV vaccination, early detection, and treatment of this virus can help women prevent its longterm and life-threatening effects, few women have the necessary knowledge and awareness to do so.…”
Section: Discussionmentioning
confidence: 99%
“…1 Another important parental barrier that has been well-documented is the fear that HPV vaccination may condone or lead to more promiscuous sexual behaviors in sons and daughters. 29 Though these thought processes present a significant challenge to immunizing clinicians, it should be noted and communicated to parents that there have been several studies which found no link between HPV vaccination and an increase in or risky sexual behavior, [30][31][32][33] and no evidence has been found to date which establishes any correlation. 34 Although parental barriers have been extremely well documented in the literature, the methodology of most studies designed to reveal these barriers still leave questions and gaps in the full picture of poor vaccine uptake.…”
Section: Hpv and Parentsmentioning
confidence: 99%
“…The quadrivalent HPV (4vHPV) vaccine was licensed and became available in the United States in 2006 for females, in 2009 for males to prevent genital warts, and in 2011, recommended routinely for males (Coyne‐Beasley & Hochwalt, 2016; Petrosky et al., 2015). In 2009, the bivalent HPV vaccine (2vHPV) became available for cervical cancer prevention (FDA, 2009) and in 2014, the nonavalent HPV vaccine (9vHPV) was introduced (Petrosky et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, the bivalent HPV vaccine (2vHPV) became available for cervical cancer prevention (FDA, 2009) and in 2014, the nonavalent HPV vaccine (9vHPV) was introduced (Petrosky et al., 2015). The goal of 4vHPV is to protect against genital warts and cervical cancer, and both 4vHPV and 9vHPV protect against vaginal, vulvar, and anal cancer (Coyne‐Beasley & Hochwalt, 2016). It is recommended that a series of two shots should be administered to those 9–14 years of age and a series of three shots should be administered to those 15–26 years of age (ACOG, 2017).…”
Section: Introductionmentioning
confidence: 99%